Tectono-sedimentary setting of the oligocene-early miocene deposits on the betic-rifian internal zone (Spain and Morocco). - Serrano, Francisco; Guerra-Merchán, Antonio; El Kadiri, Khalil; Sanz de Galdeano, Carlos; López-Garrido, A. C.; Martín-Martín, Manuel; Hlila, Rachid (Geobios, 2007)
We present here an overview of the Oligocene-early Miocene transgressive cover of the Betic-Rifian Internal Zone (BRIZ). Biostratigraphic data, depositional environment and stratigraphical correlations are here inferred based upon the planktonic foraminifera. The studied transgressive cover developed in two successive groups, which were generally deposited in the same depocenters. The older group (Ciudad Granada group, late Oligocene-Aquitanian pro-parte) unconformably rests over the Malaguide-Ghomaride Complex, while the younger one (Viñuela group, early Burdigalian) can either lie over Ciudad Granada group (central depositional areas) or rest on the Malaguide-Ghomaride and/or Alpujarride-Sebtide complexes (marginal areas). It is noteworthy that no major sedimentary gap nor unconformity were evidenced between these two groups in the central depositional areas, so no major nappe structuring may be suggested during this depositional time span. The stacking pattern of these sedimentary groups, the facies change evidenced between the bordering and the central successions, as well as some synsedimentary tectonic features recorded at their base levels, suggest that they corresponded to transgressive pulses induced by transtensive tectonics, which were related to both the opening of the Algero-Provençal and Alboran basins, and the westward migration of the BRIZ. Peer reviewed